Development Status and Prospect of Green and Environment-Friendly Water Treatment Technology - Liu Ruiyang; Niu Honghao; Qiu Zirui (MATEC Web of Conferences)
With the development of the global economy and population growth, the problem of water resources shortage and water pollution is becoming increasingly serious. Traditional water treatment technology faces challenges due to high energy consumption, secondary pollution risk, and insufficient capacity to treat complex pollutants. Although green water treatment technology shows some potential, it still faces many challenges in its application. This paper systematically reviews the development status and future trend of green water treatment technology and discusses the advantages and disadvantages of existing technology through case analysis and technical classification research of the Beijing Huaifang reclaimed Water Plant, including physical, chemical, biological, and membrane separation technology. The study found that the current technology has problems with membrane pollution, high energy consumption, and waste disposal, while lagging policies and regulations and weak public awareness further restrict its promotion. In the future, innovation needs to be completed by optimizing membrane materials and improving water treatment materials. The conclusion shows that green water treatment technology has a key significance in solving the global water resources dilemma, and its innovation development and market application prospects are broad.